The Rate Of Return To Investment In Education : A Case Study Of Polytechnic Diploma Graduates [LB2326.4. S131 2008 f rb]. - Shahar, Saharawati (2008)
Kajian ini bertujuan untuk mendapatkan kadar pulangan pelaburan dalam pendidikan dari aspek Teori Modal Insan.